Calycindaphines A–J, Daphniphyllum alkaloids from the roots of Daphniphyllum calycinum. Issue 16 (1st March 2021) - Yang, Ji; Liu, Xin; Fu, Jing; Lyu, Hao-Yuan; Bai, Li-Ping; Jiang, Zhi-Hong; Zhu, Guo-Yuan
Abstract : Ten new Daphniphyllum alkaloids, calycindaphines A–J (1–10 ), were isolated from Daphniphyllum calycinum . Compound 1 possesses a unique C22 skeleton with the 5/8/7/5/5 ring system and might be a key intermediate for daphhimalenine A formation. Abstract : Ten new Daphniphyllum alkaloids, calycindaphines A–J (1–10 ), together with seventeen known alkaloids were isolated from the roots of Daphniphyllum calycinum . Their structures were established by extensive spectroscopic methods and compared with data from literature. Compound 1 is a novel alkaloid with a new rearrangement C22 skeleton with the 5/8/7/5/5 ring system. Compound 2 represents the second example of calyciphylline G-type alkaloids. Compound 10 is the first example of secodaphniphylline-type alkaloid absent of the oxygen-bridge between C-25/C-29. The possible biogenetic pathways of 1 and 2 were also proposed. All the isolated compounds were evaluated for their bioactivities in three cell models. Compounds 22, 23, and 26 showed significant NF-κB transcriptional inhibitory activity at a concentration of 50 μM. Compounds 16 and 18 exhibited significant TGF-β inhibitory activity in HepG2 cells. Compounds 24 and 26 induced autophagic puncta and mediated the autophagic marker LC3-II conversion in HEK293 cells.